Atomistic Simulation of Na+ and Cl- Ions Binding Mechanisms to Tobermorite 14Å as a Model for Alkali Activated Cements - Abdelkawy, Ahmed (AUC Knowledge Fountain, 2022)
The production of ordinary Portland cement (OPC) is responsible for ~8% of all man-made CO2 emissions. Unfortunately, due to the continuous increase in the number of construction projects, and since virtually all projects depend on hardened cement from the hydration of OPC as the main binding material, the production of OPC is not expected to decrease. Alkali-activated cement produced from the alkaline activation of byproducts of industries, such as iron and coal industries, or processed clays represents a potential substitute for OPC. However, the interaction of the reaction products of AAC with corrosive ions from the environment, such as Cl-, remains largely unexamined. In this study, we present the details of preparing undoped and 5% Na-doped tobermorite 14Å structures as molecular models for the disordered alkali-doped calcium-alumino-silicate-hydrate (C-(N)-A-S-H, where N represents sodium and A represents aluminum) structure, which is the main reaction product in Ca-rich AAC. Moreover, we examined the ability of these structures to hinder the ingress of solvated Na+ and Cl- ions using molecular dynamics simulations. We adopted a core-shell model for these simulations to represent the polarizability of oxygen ions and a flexible model to represent water molecules. The combined interatomic interactions adopted in this work accurately predicted lattice parameters and basic mechanical properties similar to those obtained from different experimental and computational studies for the tobermorite 14Å structure. Moreover, these interactions could predict lattice parameters similar to those predicted by the ClayFF force field, a widely used force field to describe cementitious materials. By examining the structural, energetic, and dynamic properties of interfacial water molecules and solvated Na+ and Cl- ions, we showed that introducing Na+ ions as dopants to the bulk tobermorite 14Å structure had a positive impact on enhancing the adsorption of solvated Cl- ions. This positive impact is twofold; first, new and stable adsorption sites have been introduced on the surface of the 5% Na-doped system because of the charge balancing mechanism taking place while substituting Ca2+ ions with Na+ ions. Second, introducing the 5% Na+ ions led to slower dynamics for all species in this system. The slow dynamics originated from the excess Na+ ions in this system, and that NaCl is a structure-making salt. These results suggest that the presence of Na in Ca-rich AAC results in more resistance to chloride-induced corrosion due to an increased ability to hinder the movement of Cl- ions. In addition to the effectiveness of these types of cement to resist Cl- ions diffusivity, these results from molecular-scale simulations also encourage the usage of sustainable AACs, which directly reduce the immense volume of greenhouse emissions produced annually from the OPC industry.